2012
DOI: 10.4103/0028-3886.100729
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary dysfunction in survivors of spontaneous subarachnoid hemorrhage of anterior communicating artery and middle cerebral artery aneurysms: A comparative study

Abstract: Hormonal deficiencies are not uncommon in patients with SAH. There is no difference in hormonal deficiencies and severity of hypopituitarism in patients with SAH due to A-com and MCA bleed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“… 6 7 In some studies, patients were selected on the basis of symptoms of fatigue 14 or on location of the aneurysm. 15 …”
Section: Introductionmentioning
confidence: 99%
“… 6 7 In some studies, patients were selected on the basis of symptoms of fatigue 14 or on location of the aneurysm. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Dutta et al evaluated endocrine function in 60 SAH patients with anterior communicating artery (A-com) and middle cerebral artery (MCA) aneurysms using only basal hormonal tests. Part of the study was retrospective, analysing patients one year after SAH and partly prospectively analysing patients 6 months after SAH [ 46 ]. Kronvall et al prospectively analysed 45 patients in the acute phase and 3 to 6 months after SAH, using basal hormonal test and GHRH-arg test for GHD.…”
Section: Resultsmentioning
confidence: 99%
“…Blijdorp et al prospectively analysed 84 patients and reported preliminary data of 43 patients using basal hormonal tests, synacten test when ACTH deficiency was suspected and a ghrelin test in the early phase after SAH and confirmatory GHRH-arg test after six months [ 42 ]. The most prominent methodological shortcomings were the incomplete reports of patient selection [ 17 , 32 , 33 , 35 , 37 , 46 ], selection bias [ 17 , 33 - 35 , 42 , 46 ] and inadequate laboratory testing [ 17 , 33 , 35 , 36 , 38 , 43 , 44 ]. Some studies did not use dynamic tests to determine growth hormone or corticotrophin deficiency [ 17 , 34 , 43 , 44 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations